EFFECT OF FOLIAR APPLICATION OF SALICYLIC ACID, MAGNESIUM, AND IRON ON THE SEEDLIGS OF Citrus medica L. - Thkraa. S. Ahmed,; Ausama Y. Salih, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
A field experiment was carried out on Citrus medica at University of Baghdad - College of Agricultural Engineering Sciences. During the fall season of 2020 and spring season of 2021 in order to evaluate the effect of foliar application of Salicylic acid (0, 150, and 300) mg L-1, Magnesium (0, 10, and 20) mg L-1, and Iron (0, 5, and 10 mg L-1) on the vegetative growth characteristics of citron citrus medica L. seedlings local var. citronella grafted on one year old bitter orange. The experiment was conducted at Sept. 2020 until the first of July 2021 according to the factorial experiment within RCBD design that consisted of two factors and three replicates with45ex... un., for fall and spring season and a total of 90 seedlings. The results revealed a significant differences under the foliar application of salicylic acid in 150mg l-1 and 300mg l-1 in most of the studied traits, as treatment 150mg l-1 recorded the highest values of plant’s height for both seasons, and treatment 300mg l-1 recorded the highest leaves area, root’s number, leaves content of chlorophyll, leaves content of Mg and Fe, shoots content of carbohydrates for both seasons, respectively. While the foliar application of magnesium and iron, at the treatment of (10 Mg+5 Fe) mg l-1 recorded the highest values of plant’s height, leaves area for the spring season, and C/N ratio for both seasons, and leaves content of chlorophyll for the fall season. The (20 Mg+ 10Fe) mg l-1 treatment recorded the highest root Volume, leaves content of Mg and Fe; shoot’s content of carbohydrates, while the interaction treatments between the studied factors recorded the most significant values in all the studied indicators.